1987
DOI: 10.1177/000348948709600118
|View full text |Cite
|
Sign up to set email alerts
|

Epiglottoplasty for the Treatment of Laryngomalacia

Abstract: Laryngomalacia is the most common congenital laryngeal anomaly. Patients present with different degrees of stridor and feeding problems that usually resolve by 18 months of age. A small number present with severe feeding problems, failure to thrive, stridor with cyanosis, and apnea, which may result in cardiopulmonary disease. These infants require surgical intervention, usually a hyomandibulopexy or tracheotomy. We present a new procedure, epiglottoplasty, that is performed endoscopically and involves excisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
118
0
15

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(134 citation statements)
references
References 13 publications
1
118
0
15
Order By: Relevance
“…The less reliable was "not visualizing the vocal folds", in which the agreement was of 81.4%. Not being able to see the vocal folds in the videolaryngoscopic evaluation has been associated with the prognosis, because some authors use such information, together with the clinical picture, in order to indicate surgery 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The less reliable was "not visualizing the vocal folds", in which the agreement was of 81.4%. Not being able to see the vocal folds in the videolaryngoscopic evaluation has been associated with the prognosis, because some authors use such information, together with the clinical picture, in order to indicate surgery 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Two parameters must be stressed: 1) vocal folds visualization or not, because examiners with less experience in laryngology had difficulty in identifying it, and this is one of the parameters considered for surgery indication 7 ;…”
Section: Discussionmentioning
confidence: 99%
“…Geralmente é uma condição auto-limitada, mas pode produzir episódios graves de apnéia, cor pulmonale e deficiências de desenvolvimento 14 . Sua origem está ligada a imaturidade neurológica da laringe.…”
Section: Discussionunclassified
“…O curso clínico é benigno na maioria dos pacientes, e a resolução dos sintomas ocorre até os 18 meses de idade 2 . Entretanto, em alguns casos, podem haver complicações respiratórias e ser necessária a supraglotoplastia 14,15 .…”
Section: Discussionunclassified
“…Its cause is still debated. There are many theories proposed to explain its physiopathology, such as disorders in the cartilaginous framework of the larynx and trachea, causing a greater laxity in supraglottic structures, anatomical alterations and neuromuscular immaturity [18][19][20][21] . Back in 1897, Sutherland & Lack 22 proposed an anatomical theory after studying 18 cases of congenital laryngeal obstruction, in which they concluded that the disorder was associated to the immaturity of the children cartilaginous tissue.…”
Section: Introductionmentioning
confidence: 99%